Reduced Awareness of Memory Deficit is Associated With Increased Medicare Home Health Care Use in Dementia - DeFeis, Brittany (Alzheimer Dis Assoc Disord, 2019)
OBJECTIVE: The objective of this study was to examine whether reduced awareness of memory deficits in individuals with dementia is associated with more frequent need for Medicare home health care services. METHODS: Cross-sectional analyses were conducted in a multicenter, clinic-based cohort. In total, 192 participants diagnosed with dementia and their informants were independently asked whether or not the participant demonstrated cognitive symptoms of dementia related to memory and word-finding. Participant self-awareness was measured as the discrepancy between participant and caregiver report of these symptoms. Annual Medicare home health benefit use data was obtained from Medicare claims matched by year to the Predictors study visit. RESULTS: Participants that used home health services had lower awareness scores than those who did not. Awareness remained independently associated with home health use in a logistic regression adjusted for age, gender, education, caregiver relationship, global cognition, dementia subtype, and medical comorbidities. IMPLICATIONS: Reduced self-awareness of memory deficits in individuals with dementia is associated with more frequent use of Medicare home health services. The disproportionate use of in-home assistance as a function of awareness level may reflect dangers faced by patients, and challenges faced by caregivers, when patients have limited awareness of their memory deficits. Current results have implications for clinical care, caregiver education, and models of health care utilization.